SWEEP ALGORITHM IN CVRP TO OPTIMIZE DELIVERY AUTOMOTIVE SPARE PART - Alvina Putri Utami; Bonivasius Prasetyo Ichtiarto (Universitas Mercu Buana, 2021)
The CVRP to solve many optimization and application problems distribution especially of the automotive spare parts industry, West Java, Indonesia is presented has 120 customers who aim to optimize and maximize the capacity and cost of vehicles owned, namely 10 colts 6 diesel type vehicles. Vehicle routes are compared against the existing daily distribution routes showing that significant savings can be gained on the daily cost of transportation-related expenses. The objective of this research is to find a set of optimal routes that minimize the number of vehicles required and total distance traveled for all vehicles to serve customers with a result from 10 to 9 using vehicles with a total distance increase from the Sweep method of 253.8347 km and cost benefits or cost savings with a total usage cost of Rp 17.800.000 to be Rp 17,709,503 in cost efficiency of 4.47% or Rp 90,496.58 a day.